Jan Kobbernagel: Studenterforeningens historie 1890-1980, Bd. I 1890-1920, Kbh. 1984, 377 s. Bd. II 1920-1950, Kbh. 1985, 368 s., 176,- kr. pr. bd. (Nyt Nordisk Forlag) - Meyer, Poul (Historie/Jyske Samlinger, 1987)
-